Potentially Avoidable Readmissions of Patients Discharged to Post‐Acute Care: Perspectives of Hospital and Skilled Nursing Facility Staff. Issue 2 (16th December 2016) - Vasilevskis, Eduard E.; Ouslander, Joseph G.; Mixon, Amanda S.; Bell, Susan P.; Jacobsen, J. Mary Lou; Saraf, Avantika A.; Markley, Daniel; Sponsler, Kelly C.; Shutes, Jill; Long, Emily A.; Kripalani, Sunil; Simmons, Sandra F.; et al.
Abstract : Background: Hospital readmissions from skilled nursing facilities (SNFs) are common. Previous research has not examined how assessments of avoidable readmissions differ between hospital and SNF perspectives. Objectives: To determine the percentage of readmissions from post‐acute care that are considered potentially avoidable from hospital and SNF perspectives. Design: Prospective cohort study. Setting: One academic medical center and 23 SNFs. Participants: We included patients from a quality improvement trial aimed at reducing hospital readmissions among patients discharged to SNFs. We included Medicare patients who were discharged to one of 23 regional SNFs between January 2013 and January 2015, and readmitted to the hospital within 30 days. Measurements: Hospital‐based physicians and SNF‐based staff performed structured root‐cause analyses (RCA) on a sample of readmissions from a participating SNF to the index hospital. RCAs reported avoidability and factors contributing to readmissions. Results: The 30‐day unplanned readmission rate to the index hospital from SNFs was 14.5% (262 hospital readmissions of 1, 808 discharges). Of the readmissions, 120 had RCA from both the hospital and SNF. The percentage of readmissions rated as potentially avoidable was 30.0% and 13.3% according to hospital and SNF staff, respectively. Hospital and SNF ratings of potential avoidability agreed for 73.3% (88 of the 120 readmissions), but readmission factors varied between settings. Diagnostic problems and improved management of changes in conditions were the most common avoidable readmission factors by hospitals and SNFs, respectively. Conclusion: A substantial percentage of hospital readmissions from SNFs are rated as potentially avoidable. The ratings and factors underlying avoidability differ between hospital and SNF staff. These data support the need for joint accountability and collaboration for future readmission reduction efforts between hospitals and their SNF partners.